IMPROVING COMMITMENT TO ORGANIZATIONS THROUGH STRENGTHENING THE QUALITY OF WORK LIFE, TEAMWORK, ANDLEARNING ORGANIZATIONS - Messiah Prasnavidya, Bibin Rubini, Widodo Sunaryo, Zaenal Abidin (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Globalization makes competition even more dynamic, so it needs preparation to face this global competition. The emphasis lies on competitive advantage. Competitive advantage is built by building the potential for quality human resources. Human resources are the focus in increasing competitive ability through education. Better education will meet the criteria for national development. An adequate level of education can meet the required competencies, so with specific competencies it will become specializations or experts in their fields (Maseleno et al., 2019).